ON THE COMPETITIVENESS OF THE ROMANIAN TOURISM - Smaranda TOMA; Daniela MIHAI (Buletin ştiinţific: Universitatea din Piteşti. Seria Ştiinţe Economice)
Romania has improved its position in the ranking of travel and tourism competitiveness, gaining 8 positions in the last 10 years (2007-2017), which represents an important step in the direction of internationalization and development. The analysis of the current stage of the Romanian tourism competitiveness reflects its weaknesses and implicitly the necessary actions to revive tourism and to position Romania as an attractive tourist destination on the international tourism market. New approaches are required to make the progress on improving competitiveness even more evident, both from the public and private sectors, so that Romania turns into a truly international destination, recognized as such. An integrated planning of the Romanian tourism, the practical application of the concept of destination management, the collaboration between the central and regional public authorities and the private sector entities would be other actions aimed at ensuring a sustainable growth of the Romanian tourism and its competitiveness on the international tourism market.